2018
DOI: 10.1002/ccd.27997
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital outcomes of transcatheter mitral valve repair with Mitraclip in patients with pulmonary hypertension: Insights from the National Inpatient Sample

Abstract: Background Periprocedural outcomes of transcatheter mitral valve repair (TMVR) with Mitraclip in patients with pulmonary hypertension (PH) are not well studied. Methods Patients who underwent TMVR with Mitraclip between 2011 and 2015 were identified using the National Inpatient Sample (NIS). All missing variables were excluded from the analysis and therefore, complete case analysis was performed. Results A total of 1,037 patients underwent TMVR with Mitraclip between 2011 and 2015. The prevalence of PH in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Also, PASP was reduced within the first 30 days following TMVr and the reduction was independently associated with reduced 30-day or 2-year rates of HF-related hospitalization or death [ 85 ]. The finding that significant resting PH (PASP > 50 mmHg) is related to adverse clinical outcomes at the 2-year follow up in patients with HF and secondary MR, agrees with the results from previous single-center registries [ 69 , 81 , 86 ]. Matsumoto et al, demonstrated that in patients with secondary MR, TMVr with MitraClip improved the severity of the valvulopathy and symptoms [ 87 ].…”
Section: Left Ventricle Valvular Diseases and Pulmonary Hypertensionsupporting
confidence: 90%
“…Also, PASP was reduced within the first 30 days following TMVr and the reduction was independently associated with reduced 30-day or 2-year rates of HF-related hospitalization or death [ 85 ]. The finding that significant resting PH (PASP > 50 mmHg) is related to adverse clinical outcomes at the 2-year follow up in patients with HF and secondary MR, agrees with the results from previous single-center registries [ 69 , 81 , 86 ]. Matsumoto et al, demonstrated that in patients with secondary MR, TMVr with MitraClip improved the severity of the valvulopathy and symptoms [ 87 ].…”
Section: Left Ventricle Valvular Diseases and Pulmonary Hypertensionsupporting
confidence: 90%
“…In another study of patients following MitraClip implantation 120 , systolic PAP significantly decreased in patients with severe PH, but surprisingly remained unchanged in those with mild PH, and even increased in patients without PH at baseline. In-hospital outcomes did not vary significantly according to pre-existing PH in another observational study of 1037 patients undergoing MitraClip procedure 121 . However, in a larger multicentre cohort including 4071 patients undergoing MitraClip implantation, there was a clear association between preprocedural PH severity and oneyear mortality and admissions for HF, even after multivariable adjustment (HR per 5 mmHg of mean PAP increase = 1.05, 95% CI, 1.01-1.09, p = 0.02) 122 .…”
Section: Heart Diseasementioning
confidence: 88%